Academic trip on food technology - Abang, Mohamad (Universiti Teknologi MARA, Sarawak, 2016)
From 3 to 5 March 2016, 17 students taking the Diploma in Food and Technology (ASI 1 64A) in UiTM Sarawak made academic visits to the Malaysia Nuclear Agency (MNA), the Food Technology Department, UiTM Shah Alam, the UniKL MICET and also to a few international food industries in Selangor and Negeri Sembilan such as the Beryl’s Chocolate Factory and Yakult. Although the main purpose of this academic trip was to fulfil the requirement for the FST 254 Principle of Food Preservation course, it also aimed to broaden the students’ knowledge, to strengthen their relationship and also to expose them to the real situation of food technologies in Malaysia, particularly in international Halal food industries. This trip was financially funded by Tabung Amanah Pembangunan Akademik Pelajar (TAPA).